X-Ray Fluorescence (XRF) spectrometry data from a volcanic sequence from IODP Holes 369-U1513D and 369-U1513E - Lee, Eun Young; White, Lloyd T; Schnetger, Bernhard; Brumsack, Hans-Jürgen (PANGAEA, 2021)
Core samples were collected from a volcanic sequence at Holes D and E, Site U1513 on the eastern Naturaliste Plateau, offshore southwest Australia. The site was drilled by the International Ocean Discovery Program (IODP) Expedition 369 Australia Cretaceous Climate and Tectonics in 2017 (http://iodp.tamu.edu/scienceops/expeditions/australia_climate_tectonics.html). The volcanic sequence (Lithostratigraphic Unit VI) with a total cored thickness 82.2 m consists of fresh to strongly altered basalt flows and volcaniclastic beds with multiple intrusive dolerite dikes. The core samples were taken during and after the expedition and from what were deemed the most suitable and representative lithologic and alteration components of the cores. Fifty samples were selected for bulk rock X-ray fluorescence (XRF) composition analysis, which was prepared and conducted at three institutes. Standard and in-house samples were used as reference for accuracy. Fifteen core samples of Hole U1513E were analyzed using AXIOS Plus (Panalytical) at the Institute for Chemistry and Biology of the Marine Environment (ICBM), University of Oldenburg, Germany. Borate glass beads were prepared from the sample powder using di-lithium tetraborate as a flux (700 mg sample and 4.2 g flux). Additional 24 XRF datasets of Hole U1513D with the same methodology are available in the PANGAEA website (https://doi.org/10.1594/PANGAEA.924535). Twenty-seven core samples (14 samples of Hole U1513D and 13 samples of Hole U1513E) were analyzed using a Spectro Ametek XEPOS III energy dispersive XRF spectrometer at the University of Wollongong, Australia. Glass-fusion beads were analyzed to obtain major element data, recalculated to anhydrous values using the LOI measurement of each sample. Additional 8 XRF datasets with the same methodology are available in the PANGAEA website (https://doi.org/10.1594/PANGAEA.933955). Eight core samples of Hole U1513E were analyzed using AXIOS (Panalytical) at the Laboratory Center, Chonnam National University, Republic of Korea. Pellets were prepared from the sample powder mixed with wax binder (3 g sample, 0.3 g wax C18H36O2N2).
Keywords: basalt flows and volcaniclastics; East Gondwana breakup; Hole U1513D; Hole U1513E; IODP Expedition 369; IODP Site U1513; Kerguelen; Lithostratigraphic Unit VI; Mentelle Basin; Naturaliste Plateau; southwest Australia; XRF data